Obstructing Hamartomatous Polyp in Peutz-Jeghers Syndrome. (28th March 2013) - Bentley, Brian S.; Hal, Hassan M.
Abstract : A 53-year-old male presented with complaints of abdominal pain and weight loss. On physical exam he was noted to have mucocutaneous pigmentation around his lips and oral mucosa. Radiologic and endoscopic investigations demonstrated an obstructing mass in the second portion of the duodenum along with additional smaller soft tissue masses throughout the bowel. Histology of biopsied specimens revealed architectural disorganization without dysplasia, suggestive of Peutz-Jeghers hamartomatous polyps.